167 Women with early onset hypertension are more likely to have cardiac MRI findings associated with future development of heart failure than men. (4th June 2021) - Williams, Howell; Rodrigues, Jonathan; Mitrousi, Konstantina; Ormerod, Will; Walker, Dylan; Manghat, Nathan; Hart, Emma; Nightingale, Angus
Abstract : Introduction: Hypertension (HTN) is a major risk factor for developing of heart failure (HF). Patients with early onset HTN (≤40 years) are at increased risk compared to those who develop HTN in later life. The transition from HTN to HF is incompletely understood but involves left ventricular (LV) changes at the cellular level. These include diffuse interstitial fibrosis, measured by extracellular volume fraction (ECV). Elevated ECV is associated with an increased risk of death and HF hospitalisation but the extent of elevated ECV in patients with early onset HTN is not known. In addition, among patients with HF with preserved ejection fraction (HFpEF), women outnumber men by a ratio of 2:1. The reasons for this are not known. We aimed to investigate cardiac MRI parameters including ECV in patients with early onset HTN who do not have HF. Methods: Data from consecutive patients from a tertiary HTN clinic referred for CMR (Siemens, Germany) over a 3-year period was retrospectively analysed. Elevated ECV was defined as ≥28% as this is associated with increased HF hospitalisation. Data are mean ± SD. Alpha was set at 0.05. Results: 29 patients ≤40 years underwent CMR during the study period; mean age 33±5.4 years, 15/29 (52%) female.Elevated ECV was identified in 9/29 (31%) patients ≤40 years and the majority were female (8/9, p=0.01, Fisher's exact test). This gender difference was not seen in patients >40 years old with HTN who underwent CMR during the same period (29/59 [49%] had an elevated ECV with 14/29 female, p=0.19, Fisher's exact test).Among patients ≤40 years, LV hypertrophy (all concentric) was more common in those with ECV ≥28% (5/9) than those with ECV <28% (2/20, p=0.02, Fisher's exact test). Among the female patients ≤40 years, there was a trend towards increased LV mass in the 8 patients with ECV ≥28% compared to 7 with ECV <28% (78±14.4g/m2 vs 67±3.8g/m2, p=0.06, t-test).Among patients ≤40 years, there were no significant differences between the ECV ≥28% and ECV <28% groups in LV ejection fraction or LV strain, strain rate, and diastolic strain rate. There were also no differences in the parameters in table 1 . Conclusions: Among patients with early onset HTN, one in three had elevated ECV. This was independent of age, BMI, blood pressure (BP), and BP treatment. These patients are likely to be at increased risk of HF in later life.Patients with early onset HTN and an elevated ECV were more likely to be female. This may reflect an expected gender difference; recent studies indicate healthy females have higher ECV than healthy males, and this study further highlights the importance of separate ECV reference ranges for men and women. However it may also reflect early pathological fibrosis in response to HTN, particularly as in patients >40 years old there was no gender difference among patients with an elevated ECV. Increased LV fibrosis at a younger age may be a contributor to the increased development of HFpEF among female patients. Conflict of Interest: None